Microstructural evolution and compositional homogenization of a low Re-bearing Ni-based single crystal superalloy during through progression of heat treatment. (5th March 2018) - Su, Xianglin; Xu, Qingyan; Wang, Runnan; Xu, Zilin; Liu, Shizhong; Liu, Baicheng
Abstract: Microstructural and chemical heterogeneities may exacerbate the high-temperature mechanical properties of single crystal turbine blades. The evolution of microstructure and compositional homogeneity of an as-cast low Re-containing multicomponent DD6 alloy during through progression of heat treatment was detailedly studied. Using optical microscope, field emission gun scanning electron microscope, electron probe microanalysis, differential scanning calorimetry, and complementary thermodynamic calculations, we investigated the time-dependent size and volume fraction variations of γ/γ′ eutectic during specific solution heat treatment steps, the evolution of γ′ precipitates, carbides, and compositional homogeneity, and the thermo-physical changes of as-cast DD6 alloy during through progression of heat treatment. Based on our experimental and theoretical results, the mechanism underlying the microstructure formation and chemical segregation of as-cast DD6 alloy was clarified. The mechanism of microstructural evolution and compositional homogenization, and the diffusion mechanism of elements that occurs between dendritic and interdendritic regions of as-cast DD6 alloy during through progression of heat treatment were elucidated. The correlations between microstructural evolution, compositional homogenization, and thermo-physical changes of as-cast DD6 alloy during through progression of heat treatment were established. Graphical abstract: Image 1 Highlights: Microstructure formation and chemical segregation of as-cast DD6 alloy is studied. Microstructure evolution and compositional homogenization of DD6 alloy during heat treatment is investigated. Differential scanning calorimetry analysis and thermal-physical changes of DD6 alloy during heat treatment are evaluated. Correlations between microstructure evolution, compositional homogenization, and thermo-physical changes of DD6 alloy during heat treatment are established.